2008
DOI: 10.1177/004005990804000301
|View full text |Cite
|
Sign up to set email alerts
|

Mathematics Dynamic Assessment

Abstract: Ms. Carlisi teaches middle school mathematics for students who were retained at least 1 year and who were identified as at risk of failure in mathematics. About half of her class of 14 students has identified learning disabilities and/or emotional and behavioral difficulties. Ms. Carlisi worries constantly that she is not going to be able to help them “catch up” by the time they take the mandated state high-stakes standardized assessment. Ms. Carlisi knows her students need to build proficiency in fractions. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Informal STEM learning environments are naturally composed in a way to promote learning through real-world modeling and examples (Martin 2004; Meredith 2010; Popovic and Lederman 2015). Informal STEM learning environments also help students understand concepts and their ability to recall information (Allsopp et al 2007; Popovic and Lederman 2015). Participation in short-term STEM summer experiences (Bell et al 2009; Kitchen et al 2018; King 2017; Mohr-Schroeder et al 2014) or other long-term informal STEM programs (After-School Alliance 2011; Baran et al 2016; Barker et al 2014; Klanderman et al 2013; Massey and Lewis 2011) have been shown to increase students’ interest in STEM.…”
Section: Introductionmentioning
confidence: 99%
“…Informal STEM learning environments are naturally composed in a way to promote learning through real-world modeling and examples (Martin 2004; Meredith 2010; Popovic and Lederman 2015). Informal STEM learning environments also help students understand concepts and their ability to recall information (Allsopp et al 2007; Popovic and Lederman 2015). Participation in short-term STEM summer experiences (Bell et al 2009; Kitchen et al 2018; King 2017; Mohr-Schroeder et al 2014) or other long-term informal STEM programs (After-School Alliance 2011; Baran et al 2016; Barker et al 2014; Klanderman et al 2013; Massey and Lewis 2011) have been shown to increase students’ interest in STEM.…”
Section: Introductionmentioning
confidence: 99%
“…Foundations of curriculum-based measurement, instructional decision making, and other assessment practices (e.g., Allsopp et al, 2008; Fuchs, Hamlett, & Fuchs, 1999)…”
Section: Prime Online Pd Interventionmentioning
confidence: 99%
“…To successfully understand the educational needs of low maths achievers, teachers need insight into their mathematical performance, thinking, understanding, and beliefs (Deunk et al 2018). However, current maths assessment is dominated by standardised, norm-referenced testing with its focus on the products of student learning as opposed to requisite maths solving strategies, underlying thought processes, learning potential, and maths-related beliefs and emotions (Allsopp et al 2008). A promising alternative is the use of the dynamic maths interview (hereafter, DMI): a flexible, process-oriented, semi-structured assessment approach that can help identify the specific educational needs of students and particularly those with low maths achievement (Wright, Martland, and Stafford 2006;Van Luit 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we implemented a DMI within the context of inclusive maths learning in order to better identify students' maths needs (Allsopp et al 2008;Ginsberg 1997;Ginsburg 2009).…”
Section: Introductionmentioning
confidence: 99%